Igre z loparji v telesnem in gibalnem razvoju otrok v šoli - Kondrič, Miran (Šport (Ljubljana), 2018)
The morphological and motor development of the child is well monitored in the Slovenian school environment. The Sportseducational chart offers sports teachers and parents considerable information that helps in planning sports hours and observing the development of children. But how can we involve racket games in this process? Table tennis, badminton and tennis are some of the most popular recreational sports sectors. Unfortunately, they play a subordinate role in school alongside sports that fall into the "iron repertoire". These are mentioned only marginally in both primary and secondary school curricula. For this reason, we are seeing the problem of motor learning in older beginners, something that could easily be addressed in early childhood. In particular, the development of coordination, ball and racket control, perception and timeliness must become an integral part of the school curriculum.
Keywords: gibalni razvoj; igre z loparji; osnovne šole; otroci; športne igre; telesni razvoj; vzgoja in izobraževanje